Antifungal and Antibacterial Activity of Aqueous and Ethanolic Extracts of Different Rosa rugosa Parts - Žaneta Maželienė; Jolita Kirvaitienė; Kamilė Kaklauskienė; Rasa Volskienė; Asta Aleksandravičienė (Microbiology Research)
With the rising incidence of drug-resistant pathogens, focus should be placed on biologically active compounds derived from plant species used in herbal medicine, as these compounds may provide a new source of antifungal and antibacterial activities. The aim of this study was to evaluate the antifungal and antibacterial activity of ethanol and aqueous extracts from different parts of Rosa rugosa. In order to evaluate the antimicrobial activity of the extracts of R. rugosa rose hips, flowers, petals, leaves, stems, and roots, a laboratory microbiological test was performed using the well diffusion method in agar. A rotary evaporator was used for extract concentration and extractant removal. Antimicrobial activity was tested against one fungus, four Gram-positive, and four Gram-negative bacteria. The leaf extracts exhibited the strongest antimicrobial activity, followed by the extracts from the petals and rose hips, while weaker activity was observed in the root extracts. The extracts from the stems and rose hips showed the weakest effect. Ethanol extracts were more effective than water extracts. Aqueous and ethanolic extracts of R. rugosa parts demonstrated antifungal activity against Candida albicans, with ethanol extracts proving to be more effective. Among all the R. rugosa parts analyzed, the petals exhibited the strongest antifungal activity.